THE ROLE OF THE CHINESE DURING THE PHYSICAL REVOLUTION IN PALEMBANG - Putri, Nabila; Irwanto, Dedi (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
The role of Chinese people was very important in the struggle for independence during the physical revolution in Palembang from 1945 to 1949. This study aims to understand the efforts of ethnic Chinese during the revolution in Palembang, the form of ethnic Chinese assistance and the role of organizations in fighting for independence during the revolution in Palembang. The method used in this study is a qualitative approach with a historical analysis method, which involves collecting data from archives, historical documents and interviews. The results of this study indicate that the role of Chinese entrepreneurs is very important in the struggle for independence, in addition to that Chinese organizations were also involved in the struggle for independence in Palembang. This study is expected to contribute to a deeper understanding of the role of Chinese people in the struggle for independence in Palembang